Role Medicinal Plant Extracts Glossostemonbruguieriand(Moghat) On Bio-Yogurt Quality During Storage - Ramal Ahmed Mustafa (International Journal of Advanced Science and Technology, 2020)
the main point in the present investigation to produce a novel formula of bio - yogurt with different concentrations of Glossostemonbruguieriand(Moghat) extract(2.5 %, 5 %, 7.5 % and 10 %) by assessing its physicochemical gross, also influence plant extract on microbiology and sensory appearances. Also effect Moghat extract on total phenolcontented and antioxidant during when kept for 14 days.During the study changes in pH and acidity level was observed during storage.Moghat extract decline the amount of L. bulgaricusthru the storage. However, fortified yogurt with 2.5 % of Moghat extract at first day had the maximum (P< 0.05) viable count of probiotic bacteria (8.3 log cfu mL - 1). Increase hardness (g) of fortified yogurt during storage, also 10 % of Moghat extract significantly increased WHC percentage. It gave larger syneresis percentage (55.0 %) on the first day with 2.5 % of herbal extract than the other samples. Considering the sensory evaluation influenced of the Moghat extract, the best treatment with suitable flavor, appearance without any signs of spoilage.The inference of the results milk enhanced with natural extract may use as a functional dairy to improve health significantly